Recent advances in electromagnetic interference shielding properties of carbon-fibre-reinforced polymer composites—a topical review - Mikinka, E.; Siwak, M. (Journal of materials science. Materials in electronics, 2021)
Using carbon-fibre-reinforced polymer (CFRP) composites for electromagnetic interference (EMI) shielding has become a rapidly emerging field. This state-of-the-art review summarises all the recent research advancements in the field of electromagnetic shielding properties of CFRP composites, with exclusive attention paid to experimental work. It focuses on (1) important mechanisms and physical phenomena in the shielding process for anisotropic carbon-fibre composites and (2) shielding performance of CFRP materials as reported in the literature, with important performance-affecting parameters. The key properties which directly influence the shielding performance are identified, the most critical being the carbon-fibre concentration along with length for discontinuous carbon-fibre-filled polymers and the lay-up for continuous carbon-fibre-reinforced composites. The effect of adding conductive inclusions such as metal or carbon nanotubes is also reviewed. It is emphasised that processing conditions are strongly linked with the shielding properties of a composite. This is a first review, which covers all the recent advancements in the field of shielding properties of carbon-fibre-reinforced composites, with detailed analysis of factors influencing these properties and clear distinction between continuous and discontinuous reinforcement. It is shown that CFRP composites make a good candidate as an EMI shielding enclosure material.